Both Acidic pH Value and Binding Interactions of Tartaric Acid With α-Glucosidase Cause the Enzyme Inhibition: The Mechanism in α-Glucosidase Inhibition of Four Caffeic and Tartaric Acid Derivates - Li, Wenyue; Song, Yi; Sun, Wanshu; Yang, Xi; Liu, Xuebo; Sun, Lijun (Frontiers in Nutrition, 2021)
The inhibition mechanism of four caffeic and tartaric acid derivates, including caffeic acid (CA), tartaric acid (TA), caftaric acid (CFA) and chicoric acid (CHA) against α-glucosidase was characterized by substrate depletion, fluorescence quenching, isothermal titration calorimetry (ITC) and molecular docking. TA and CA were found with the highest and no inhibition effect respectively, and caffeoyl substitution at 2 and/or 3-OH of TA significantly decreased its inhibition. The enzyme inhibition effects of organic acids were not in an inhibitor concentration-dependent mode, and there was a rush increase in inhibition at a respective acidic pH value, especially for CFA and CHA, suggesting the important role of acidic pH in the enzyme inhibition for both compounds. Besides, CA, CFA and CHA were shown with strong quenching effects on α-glucosidase fluorescence because of π-conjugations between aromatic ring of caffeoyl moiety and that of enzyme fluorescent residues. However, no fluorescence quenching effect was observed for TA due to lack of aromatic ring. Additionally, a direct binding interaction behavior was observed for TA with α-glucosidase according to the fitted independent binding model in ITC, but not for CFA and CHA. Therefore, both acidic pH and binding interactions of TA with α-glucosidase resulted in the enzyme inhibition.